2017
DOI: 10.4401/ag-7059
|View full text |Cite
|
Sign up to set email alerts
|

A Combined Velocity Field of the Mediterranean Region

Abstract: We present a full 3-D velocity field of the Earth's surface in the Euro

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
112
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 133 publications
(125 citation statements)
references
References 34 publications
13
112
0
Order By: Relevance
“…Owing to the occurrence of active subduction processes (Carminati & Doglioni, ), the Italian peninsula is characterized by two major mountain chains (the Alps and the Apennines that continue in western Sicily, where the Apennines merge into the Maghrebian chain; Figure a; Dewey et al, ; Malinverno & Ryan, ; Doglioni, ; Doglioni et al, ; Faccenna et al, ; Rosenbaum & Lister, ; Carminati et al, ; Carminati & Doglioni, ). The Southern Alps and the Apennines accretionary prism show active contraction as indicated by deformation of sediments, seismicity (Figure a) and global positioning system data (Devoti et al, and references therein). Unlike Pacific and East Asia subduction zones, where convergence rates are up to 10 cm/year (e.g., Lallemand et al, ); along the Alpine and Apennines subduction zones, convergence rate is much slower and varies between 1 and 3 mm/year (Devoti et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Owing to the occurrence of active subduction processes (Carminati & Doglioni, ), the Italian peninsula is characterized by two major mountain chains (the Alps and the Apennines that continue in western Sicily, where the Apennines merge into the Maghrebian chain; Figure a; Dewey et al, ; Malinverno & Ryan, ; Doglioni, ; Doglioni et al, ; Faccenna et al, ; Rosenbaum & Lister, ; Carminati et al, ; Carminati & Doglioni, ). The Southern Alps and the Apennines accretionary prism show active contraction as indicated by deformation of sediments, seismicity (Figure a) and global positioning system data (Devoti et al, and references therein). Unlike Pacific and East Asia subduction zones, where convergence rates are up to 10 cm/year (e.g., Lallemand et al, ); along the Alpine and Apennines subduction zones, convergence rate is much slower and varies between 1 and 3 mm/year (Devoti et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, on 30 October, a third large event of magnitude M w 6.5 nucleated below the town of Norcia, striking the area between the two preceding events and filling the gap between the previous ruptures. Fault plane solutions for the main events exhibit normal faulting (http://cnt.rm.ingv.tdmt) consistent with the direction of active extension of~3-4 mm/yr in this sector of the Apennines [Petricca et al, 2015;Devoti et al, 2017]. Previous geological studies [Boncio et al, 2004;Galli et al, 2008;Pizzi and Galadini, 2009] have identified several NW-SE trending normal fault systems, which are active in this area, and are often segmented by preexisting tectonic structures inherited from the pre-Quaternary compressional tectonic phases [Pizzi and Galadini, 2009].…”
Section: Introductionmentioning
confidence: 99%
“…In Experiment #1 we inverted GPS measurements from Devoti et al (2017) under the assumption that the megathrust is unlocked and creeping steadily, which implies that interseismic coupling is zero, to determine (a) the long-term heave rates of all upper-plate faults comprising the NW dipping data set and (b) the heave rate of the subduction interface. In Experiment #1 we inverted GPS measurements from Devoti et al (2017) under the assumption that the megathrust is unlocked and creeping steadily, which implies that interseismic coupling is zero, to determine (a) the long-term heave rates of all upper-plate faults comprising the NW dipping data set and (b) the heave rate of the subduction interface.…”
Section: Kinematic Modeling: Alternative Scenarios For the Long-term mentioning
confidence: 99%
“…We acknowledge Roberto Devoti for providing us with GPS horizontal velocities (published in Devoti et al, 2017). name/oldFTP/NeoKinema/.…”
Section: Acknowledgmentsmentioning
confidence: 99%